Stages and maintasks of the century-long control theory and system identification development. PartVII. Multirate sampling control systems - Romanenko, V.; Gubarev, V. (Проблеми керування та інформатики, 2024)
The article provides a review and generalization of the main approaches and methods of designing discrete controllers with multirate sampling for multidimensional and multi-connected control objects described by models in the state space, which have the property of functioning in two time scales. Зроблено огляд основних підходів та методів проєктування дискретних регуляторів з різнотемповою дискретизацією для багатовимірних та багатозвʼязних обʼєктів керування, описаних моделями у просторі стану, які мають властивість функціонування у двох масштабах часу, та представлено їхнє узагальнення.